2015
DOI: 10.1007/s10071-015-0937-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the production of self-directed behavior by chimpanzees and gorillas during a computerized cognitive test

Abstract: Self-directed behaviors (SDBs) are a commonly used behavioral indicator of arousal in nonhuman primates. Experimental manipulations, designed to increase arousal and uncertainty, have been used to elicit SDB production in primates. Beyond measuring rates of SDB production, researchers have also recorded their lateralized production by primates, thought to reflect laterality of hemispheric brain control and response to emotion. Although a handful of such studies exist, all have been conducted with chimpanzees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…The chimpanzees lived together in a social group of six. All subjects had previous experience viewing stimuli on a touch-screen monitor38.…”
Section: Discussionmentioning
confidence: 99%
“…The chimpanzees lived together in a social group of six. All subjects had previous experience viewing stimuli on a touch-screen monitor38.…”
Section: Discussionmentioning
confidence: 99%
“…The SimChain paradigm has been used in several species (Terrace, 1993; Wagner, Hopper, & Ross, 2015), with immature and adult individuals (Inoue & Matsuzawa, 2009); the task is repeatable and informative. Distinct cognitive tasks are likely to tap into general or domain specific intelligences to varying degrees, and since it is not known how many factors are best for modeling macaque intelligence, it remains an open question which domains SimChain performance draws on.…”
Section: Discussionmentioning
confidence: 99%
“…The subject for this evaluation was a 12year-old male gorilla (Gorilla gorilla gorilla) who lived in an all-male group comprising four gorillas (average age: 10.8 years) at the Lincoln Park Zoo, Chicago, USA. As with many of the apes at the Lincoln Park Zoo, prior to this study the subject had had several years of experience using touchscreen computers, specifically with serial-learning tasks (e.g., Wagner, Hopper, & Ross, 2016), but had never before been shown photographs of real-life objects on the touchscreen, nor had he participated in preference testing using the touchscreen. Previous preference testing, in which the subject was manually offered two foods simultaneously in a forced choice paradigm (sensu Hopper et al, 2015), had revealed that this gorilla preferred grapes over pieces of carrot, but no other food preferences had been formally tested.…”
Section: Subject and Housingmentioning
confidence: 99%